2005
DOI: 10.1111/j.1365-313x.2005.02342.x
|View full text |Cite
|
Sign up to set email alerts
|

New pOp/LhG4 vectors for stringent glucocorticoid‐dependent transgene expression in Arabidopsis

Abstract: These authors contributed equally to this work. SummaryTo facilitate glucocorticoid-inducible transgene expression from the pOp promoter in Arabidopsis the ligandbinding domain of a rat glucocorticoid receptor (GR LBD) was fused to the amino terminus of the synthetic transcription factor LhG4 to generate LhGR-N. Fusions bearing the GR LBD at other positions in LhG4 exhibited incomplete repression or inefficient induction. LhGR-N was stringently repressed in the absence of exogenous glucocorticoid but was fully… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
301
0
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 199 publications
(316 citation statements)
references
References 97 publications
12
301
0
3
Order By: Relevance
“…Although the depth of sinus indentation was clearly increased towards the base of the leaves, a smaller change was observed towards the leaf tip, suggesting that the basic pattern of lobbing/serration was not altered by these manipulations. The pOp synthetic promoter used in these experiments (Craft et al, 2005;Samalova et al, 2005) resulted in simultaneous transcription of AtKRP1 and a GUS reporter gene after Dex induction, allowing verification that target gene expression was localized to the expected region of the leaf flank ( Figure S1d-g). Analysis of leaf histology showed that the cells in the region of CUC2-directed AtKRP1 expression were greatly enlarged relative to adjacent cells (Figure 2e-g) and relative to cells in equivalent positions in wild-type leaves (Figure 2c).…”
Section: Inhibition Of Growth In the Cuc2 Domain Leads To Leaf Lobingmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the depth of sinus indentation was clearly increased towards the base of the leaves, a smaller change was observed towards the leaf tip, suggesting that the basic pattern of lobbing/serration was not altered by these manipulations. The pOp synthetic promoter used in these experiments (Craft et al, 2005;Samalova et al, 2005) resulted in simultaneous transcription of AtKRP1 and a GUS reporter gene after Dex induction, allowing verification that target gene expression was localized to the expected region of the leaf flank ( Figure S1d-g). Analysis of leaf histology showed that the cells in the region of CUC2-directed AtKRP1 expression were greatly enlarged relative to adjacent cells (Figure 2e-g) and relative to cells in equivalent positions in wild-type leaves (Figure 2c).…”
Section: Inhibition Of Growth In the Cuc2 Domain Leads To Leaf Lobingmentioning
confidence: 99%
“…The amplified fragment was subsequently cloned into the pENTR-DTOPO vector, and then recombined into the pBIN-LRLhGR2 vector using LR clonase (Invitrogen). For the second component of the CUC2>>KRP1 plants, SalI and BamHI restriction sites were added to a KRP1 109 fragment using primers 5¢-acgcGTCGACATGGAATTTGAATCGGCGGTTAAAG-3¢ and 5¢-acgcGTCGACATGGTGAGAAAATATAGAAAAGCT-3¢, and, after restriction digest, fragments were ligated into a pV-TOP vector (Craft et al, 2005) using T4 DNA ligase (Promega). After transformation into Arabidopsis (Clough and Bent, 1998), homozygous progeny for each component (pBIN-CUC2-LR-LhGR2 and pV-TOP-KRP1) were obtained and crossed.…”
Section: Dna Cloning and Transgenic Plantsmentioning
confidence: 99%
See 1 more Smart Citation
“…The aim was to measure transcriptome changes following induction. A twocomponent glucocorticoid-inducible system was used to drive GLK1 or GLK2 expression following treatment with dexamethasone (DEX) (Craft et al, 2005). Briefly, the GLK1 and GLK2 coding sequences were cloned behind a chimeric promoter consisting of a minimal cauliflower mosaic virus 35S promoter and six ideal lac operator sequences, termed pOp6 (Kannangara et al, 2007).…”
Section: Induction Of Glk1 and Glk2 Leads To Increased Levels Of Chlomentioning
confidence: 99%
“…The activator line LhGR-N(4c), carrying a single copy of the 35S:LhGR-N construct (Craft et al, 2005), was crossed with the glk1 glk2 mutant. The dark-green F1 progeny were selected on kanamycin and selfed.…”
Section: Plant Materials and Growth Conditionsmentioning
confidence: 99%